Tinjauan Kelembagaan Dewan Pengawas Syariah dari Aspek Nomenklatur, Kedudukan di Lembaga Perbankan dan Remunerasi - Aziz, Abdul (Sharia Faculty Islamic Economic Law Study Department, 2021)
DPS is a key institution that ensures the operational activities of sharia financial institutions are in accordance with sharia principles. In order to streamline the implementation of DPS duties, efforts are needed to increase knowledge of banking operations, as well as the intensity of its involvement in outreach programs for local residents. In practice, there are still many problems that cause the supervisory aspect not to be optimal as expected. This is caused by several factors, both internal and external. This study aims to determine the institutional review of DPS in terms of nomenclature, position in banking institutions and remuneration. The research method used in this research is literature review sourced from books, articles, internet and opinions of experts in accordance with the discussion. In according to the nomenclature, DPS in Indonesia would be more appropriate to use the term Sharia Advisory Board instead of the Sharia Supervisory Board. Meanwhile, in terms of position in banking institutions, DPS should only be allowed to serve in one financial institution so as not to create a conflict of interest between one financial institution and another. Whereas in terms of remuneration, it should be that which determines and provides remuneration to DPS is the association of sharia financial institutions such as the Association of Indonesian Sharia Banks (ASBISINDO), the Association of All Indonesian BMTs (ABSINDO), and others so as not to cause objectivity in implementation of duties because it will inevitably be biased in making decisions.